REGIONAL VACCINATION PROGRAMME: WAYS TO ESTABLISH, RESULTS AND PROSPECTS - O.P. Kovtun; V.V. Romanenko; N.V. Kazakevich; N.V. Savvina (Union of pediatricians of Russia, 2010)
The article describes a step-by-step strategy for establishing a regional vaccination programme. The authors draw attention to the need for expansion of the National Schedule given the current domestic epidemiological situation - a significant increase in the frequency of severe pneumonias, meningitis, otitis and their complications. It provides examples of immunization programmes in the Sverdlovsk region, Tyumen, Republic of Sakha (Yakutia), shows the importance of the regional component in the National Immunizations Schedule as an effective tool to control infectious disease incidence in the area. Key words: regional programme of vaccination, vaccinoprophylaxis, infection control, children, pneumococcal infection. (Pediatric Pharmacology. - 2010; 7(4):19-23)